Functional Connectivity Between the Trigeminal Main Sensory Nucleus and the Trigeminal Motor Nucleus - Slaoui Hasnaoui, Mohammed; Arsenault, Isabel; Verdier, Dorly; Obeid, Sami; Kolta, Arlette (Frontiers in Cellular Neuroscience, 2020)
The present study shows new evidence of functional connectivity between the trigeminal main sensory (NVsnpr) and motor (NVmt) nuclei in rats and mice. NVsnpr neurons projecting to NVmt are most highly concentrated in its dorsal half. Their electrical stimulation induced multiphasic excitatory synaptic responses in trigeminal MNs and evoked calcium responses mainly in the jaw-closing region of NVmt. Induction of rhythmic bursting in NVsnpr neurons by local applications of BAPTA also elicited rhythmic firing or clustering of postsynaptic potentials in trigeminal motoneurons, further emphasizing the functional relationship between these two nuclei in terms of rhythm transmission. Biocytin injections in both nuclei and calcium-imaging in one of the two nuclei during electrical stimulation of the other revealed a specific pattern of connectivity between the two nuclei, which organization seemed to critically depend on the dorso-ventral location of the stimulation site within NVsnpr with the most dorsal areas of NVsnpr projecting to the dorso-lateral region of NVmt and intermediate areas projecting to ventro-medial NVmt. This study confirms and develops earlier experiments by exploring the physiological nature and functional topography of the connectivity between NVsnpr and NVmt that was demonstrated in the past with neuroanatomical techniques.